(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
What does a disabled young person need? Is it a difficult question? The answer is definitely not one. A young person who lives with a disability needs exactly the same things like his peers: a home, a job, income, well-spent leisure time, friends, a partner, a family, and health care. What actually makes this listing different is that in order to achieve all these things these young people also need support from others. Parents raising a child with a disability dream about offering assisted living to their children in adulthood. This sort of assisted living has no tradition in Hungary. The best example in the country would be the network of institutes,”Down Foundation Helping the Development of the Intellectually Disabled”. This organization embraces the whole life span of disabled people from birth to old age.